Transcriptional Analysis for Tuberculosis in Pregnant Women From the PRegnancy Associated Changes In Tuberculosis Immunology (PRACHITi) Study. (10th June 2022) - Mathad, Jyoti S; Queiroz, Artur T L; Bhosale, Ramesh; Alexander, Mallika; Naik, Shilpa; Kulkarni, Vandana; Andrade, Bruno B; Gupta, Amita
Abstract: A new tuberculosis (TB) diagnostic cartridge assay, which detects a 3-gene TB signature in whole blood, was not diagnostic in women with maternal TB disease in India (area under the curve [AUC] = 0.72). In a cohort of pregnant women, we identified a novel gene set for TB diagnosis (AUC = 0.97) and one for TB progression (AUC = 0.96).